A Ral Guanine Exchange Factor-Ral Pathway Is Conserved in Drosophila melanogaster and Sheds New Light on the Connectivity of the Ral, Ras, and Rap Pathways - Mirey, Gladys (American Society for Microbiology, 2003)
Ras GTPases are central to many physiological and pathological signaling pathways and act via a combination of effectors. In mammals, at least three Ral exchange factors (RalGEFs) contain a Ras association domain and constitute a discrete subgroup of Ras effectors. Despite their ability to bind activated Rap as well as activated Ras, they seem to act downstream of Ras but not downstream of Rap. We have revisited the Ras/Rap-Ral connections in Drosophila melanogaster by using iterative two-hybrid screens with these three GTPases as primary baits and a subsequent genetic approach. We show that (i) the Ral-centered protein network appears to be extremely conserved in human and flies, (ii) in this network, RGL is a functional Drosophila orthologue of RalGEFs, and (iii) the RGL-Ral pathway functionally interacts with both the Ras and Rap pathways. Our data do not support the paradigmatic model where Ral is in the effector pathway of Ras. They reveal a signaling circuitry where Ral is functionally downstream of the Rap GTPase, at odds with the pathways described for mammalian cell lines. Thus, in vivo data show variations in the connectivity of pathways described for cell lines which might display only a subset of the biological possibilities.